2014
DOI: 10.1063/1.4898140
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying lubricant droplet spreading on a flat substrate using molecular dynamics

Abstract: Understanding the physical behavior of polymer-based lubricants on the nanoscale is of critical importance to a myriad of engineering applications and devices. We have used molecular dynamics simulations to quantitatively evaluate the physical mechanisms underlying perfluoropolyether lubricant spreading on a solid substrate. We quantify the effect of molecular mass, molecule length, and lubricant and substrate functional end groups on lubricant spreading. The results show that lubricant functional end groups p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
10
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 23 publications
6
10
1
Order By: Relevance
“…The polymer molecules do not remain entangled because a molecule length of N = 10 is below the critical entanglement length, initially established for a primitive chain by Kremer et al 36 and previously identified for our model as N ≈ 20. 32,37 The insets in Figure 2b show the corresponding pressure (side view, averaged over 500 000 time steps) and entanglement (top view) maps (color scale provided). The pressure map insets depict an area of high pressure at the center base of the droplet at the inception of spreading, which creates a pressure difference that drives the molecules outward.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The polymer molecules do not remain entangled because a molecule length of N = 10 is below the critical entanglement length, initially established for a primitive chain by Kremer et al 36 and previously identified for our model as N ≈ 20. 32,37 The insets in Figure 2b show the corresponding pressure (side view, averaged over 500 000 time steps) and entanglement (top view) maps (color scale provided). The pressure map insets depict an area of high pressure at the center base of the droplet at the inception of spreading, which creates a pressure difference that drives the molecules outward.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…However, controlling spreading and coverage of an ultrathin liquid polymer film is challenging because surface forces, as opposed to body forces like gravity, dominate on the nanoscale. Several research groups, including ours, have studied polymer spreading on a flat substrate [5][6][7][8][9], whereas only a few research groups have studied polymer spreading on a surface with nanoscale topographical features, despite evidence that such features significantly affect polymer spreading.…”
Section: Introductionmentioning
confidence: 99%
“…The bead mass is 0.2 kg/mol; thus, the molecular weight is 2 kg/mol. The potential function interactions that define the system are similar to validated potentials used in previous research and are discussed in detail in the Supporting Information (SI). , , Gravity is negligible at this scale and, therefore, not included in our model.…”
Section: Methodsmentioning
confidence: 99%
“…However, no publications seem to exist that provide a complete molecular-level explanation of how nanoscale textures affect polymer spreading and how texture peaks and texture grooves alter the wettability of a substrate. Thus, the objective of this work is to quantify polymer spreading on unidirectional nanotextured substrates and to provide a molecular-level explanation of polymer spreading on nanotextured substrates, as compared to a flat substrate, which we have studied previously. We perform MD simulations of liquid polymer spreading on rigid substrates with unidirectional nanotexture features of various shapes and sizes.…”
Section: Introductionmentioning
confidence: 99%